Psychological Emotion and Behavior Analysis in Music Teaching Based on the Attention, Relevance, Confidence, and Satisfaction Motivation Model - Li, Dong (Frontiers in Psychology, 2022)
The abbreviation ARCS in the ARCS motivational model comprises the first letters of four English words: Attention, Relevance, Confidence, and Satisfaction. The ARCS motivation model is based on a systematic and easy-to-operate motivation theory. Many research studies have verified the applicability and effectiveness of the ARCS model in education worldwide. The proposed optimized ARCS motivation model takes the traditional ARCS motivation model and systematically optimizes it to make it suitable for the coding of data from videos of music classes. The case analysis method selected 14 high-quality music lessons as the research object. The optimized ARCS model involves text conversion, coding, and statistical analysis of the transcripts of videos of high-quality music classes. The data analysis was used to analyze the characteristics of students’ emotional and behavioral motivation incentive strategies in each section of the ARCS motivation model in combination with specific high-quality case lesson fragments. This paper summarizes ways and means of using a motivational approach in the teaching of quality music classes, providing theoretical support for the practice of music teaching.